1991
DOI: 10.1128/jb.173.18.5800-5807.1991
|View full text |Cite
|
Sign up to set email alerts
|

Integration host factor binds specifically to multiple sites in the ompB promoter of Escherichia coli and inhibits transcription

Abstract: Escherichia coli integration host factor (IHF) is a DNA-binding protein that participates in gene regulation, site-specific recombination, and other processes in E. coli and some of its bacteriophages and plasmids. In the present study, we showed that IHF is a direct negative effector of the ompB operon of E. coli. Gel retardation experiments and DNase I footprinting studies revealed that IHF binds to three sites in the ompB promoter region. In vitro transcription from ompB promoter fragments was specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

1992
1992
1999
1999

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 52 publications
0
35
0
1
Order By: Relevance
“…The initial experiments were done in cells containing an IHF mutation in order to increase the possibility of detecting ompB transcripts. Strains deficient in IHF have been shown to have increased ompB expression (49). The data in Fig.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…The initial experiments were done in cells containing an IHF mutation in order to increase the possibility of detecting ompB transcripts. Strains deficient in IHF have been shown to have increased ompB expression (49). The data in Fig.…”
Section: Resultsmentioning
confidence: 60%
“…During a study of binding of IHF to sites in the ompB promoter region (49), we noted a potential cyclic AMP-CRP binding site immediately upstream of the -35 region of the ompB promoter identified in vitro ( Fig. 1) (49). To investigate whether cyclic AMP-CRP influences ompB expression in vivo, we used strain JMS65, which has a chromosomal fusion between the promoter and first structural gene of ompB and lacZ.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The integration host factor and Fis proteins are known to be involved in regulation of a variety of genes in E. coli (40,46). We tested if these proteins affect fumA and fumC expression (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, OmpR levels are elevated in the parent strain grown in high-osmolarity medium and in the envZ473 and envZJl (10) strains. Although the regulation of the ompB operon has not been well studied, it has been suggested that integration host factor may play a role in modulating the steady-state levels of OmpR in the cell, which may, in turn, affect ompF and ompC regulation (30). Future studies on the regulation of ompB and the effect that elevated levels of OmpR have on porin gene expression should provide greater insight into the molecular mechanism by which ompF and ompC are regulated.…”
Section: Discussionmentioning
confidence: 99%